DNA barcoding of Schizothorax species from the Neelum and Jhelum Rivers of Azad Jammu and Kashmir. Issue 1 (1st January 2016) - Akhtar, Tasleem; Ali, Ghazanfar
Abstract: The mitochondrial Cytochrome Oxidase 1 gene is used as a standardized, authenticated, and reliable genetic marker for a global species-level bio-identification system. The present study was conducted to determine whether barcoding can help accurate species identification in fishes. The overall base composition of Schizothorax species was 29.6% of T, 25.5% of C, 26.5% of A, and 18.4% of G, A + T content 56.1% and G + C content 43.9%. The T s/ T v bias ( R ) was 2.51. Complete COI gene was amplified using PCR and sequenced from 17 samples collected from river Neelum and Jhelum, and identification of species were done by following Mirza (1991 ), Jhingran (1991 ) classification and also through BOLD (99.3 to 99.9%) and NCBI (99.6 to 99.9%) reference sequences of those species. Multiple alignments of CO1 mtDNA gene resulted in a range of 1535–1551 base pairs. Out of 1535 consensus sites, 1490 were constant, 61 characters were variable, in which 54 were parsimony informative, and 7 variables were parsimony uninformative. This is the very first study reported from a reservoir of cold water bodies of Azad Kashmir which have a great potential for conservation of cold water fish species. We emphasized that, DNA barcoding is an accurate, reliable and has the great potential for identification of freshwater fish species.